The Equilibrium Real Exchange Rate in a Commodity Exporting Country : The Case of Russia. (IMF Working Papers; Working Paper ;, 2003)
Questions about external competitiveness, exchange rate misalignment, and the appropriate exchange rate policy feature prominently in the Russian policy debate. This paper furthers the debate by estimating empirically Russia's equilibrium real exchange rate (ERER)-that is, the rate consistent with the long-run economic fundamentals-and sheds light on the extent to which exchange rate policy should be changed. The paper confirms that the ERER reflects both productivity and the terms of trade. It suggests that Russia should target a significant medium-term current account deterioration and a real appreciation perhaps exceeding 10 percent. However, this latter number remains very sensitive to the assumed long-run oil prices.